PENYULUHAN TENTANG POTENSI LAHAN PEKARANGAN UNTUK PENINGKATAN PENDAPATAN DAN KERAGAMAN PANGAN PETANI DI LAHAN PASANG SURUT DESA SAWAHAN KABUPATEN BARITO KUALA - Hartoni ,; Ditahardiyani ,; K. A. Shafriani (Buletin Udayana Mengabdi, 2023)
The community service, which was carried out in Sawahan Village, Cerbon District, Barito Kuala Regency, aimed to convey information about the potential of farmers' yard land to increase household income and provide diversity of food that can be consumed by farmer families. The problem that is the cause of this service is the use of yard land which is still not optimal, due to the lack of knowledge of farmers in utilizing the yard land. The method of implementation of the service activities carried out is in the form of discussions and questions and answers, compiled by taking into account socio-cultural, economic, and community life aspects. Through this service activity, service participants gain additional knowledge about the use of the yard appropriately, so that they can contribute to household income and provide additional choices of types of food that can be consumed by farming families. Through this service activity, farmers become motivated to make optimal use of yard land. Farmers' responses to the innovation information submitted tend to be very good based on the properties of the innovation. Keywords: innovation, food diversity, yard land, tidal land, income